The Practice and Process of Delivering Integration through Strategic Planning - Jarzabkowski, Paula; Balogun, Julia (Journal of Management Studies, 2009)
abstractThis paper explains how strategic planning is able to deliver strategic integration within organizations. While communication and participation within planning processes are perceived to have an integrative effect, we argue that these effects are unlikely to arise simply from bringing people together. Rather, we suggest that, given the varying interests of actors in different business units, integration will only arise from active negotiations and compromises between these actors. The paper is based upon a case of strategic planning in a multinational that was attempting to develop greater strategic integration across Europe. Drawing upon an activity theory framework, we examine how a common strategy emerges over time through modifications to the planning process and to different actors' roles within it. The findings are used to develop a process model that shows how different business unit characteristics of planning experience and relative power shape different experiences of communication and participation activities and different processes for achieving integration. The paper concludes with a discussion of how this process model contributes to the literature on strategic planning, political processes of strategy‐making, and strategy‐as‐practice.